2008
DOI: 10.1164/rccm.200705-675oc
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Neutrophil Apoptosis in Patients with Sleep Apnea

Abstract: Decreased apoptosis and increased expression of adhesion molecules were noted in OSA PMNs. Although adhesion molecules may facilitate increased PMN-endothelium interactions, decreased apoptosis may further augment these interactions and facilitate free radical and proteolytic enzyme release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 57 publications
5
91
0
2
Order By: Relevance
“…However, the uncontrolled release of their formidable array of toxic substances may inflict damage on the surrounding tissues and propagate inflammatory responses, leading to tissue scarring and destruction. Normally, PMNs are removed by apoptosis to limit their activation [25] . When PMNs die by apoptosis, they retain their granular contents but lose chemotactic and secretory responsiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the uncontrolled release of their formidable array of toxic substances may inflict damage on the surrounding tissues and propagate inflammatory responses, leading to tissue scarring and destruction. Normally, PMNs are removed by apoptosis to limit their activation [25] . When PMNs die by apoptosis, they retain their granular contents but lose chemotactic and secretory responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…These PMNs are recognized and phagocytosed by macrophages. Thus, by down-regulating the potentially harmful PMN functions and triggering their clearance by phagocytes, apoptosis provides a mechanism for the safe removal of inflammatory cells [25] . Moreover, studies in recent years have shown that the inhibition and delay of PMN apoptosis occurs in the lung tissue during ALI, which leads to the prolonged release of PMN products and direct tissue injury [15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further evidence for a pro-survival effect of HIF-1a is provided by the delayed apoptosis of human neutrophils observed when HIF is stabilised, either by loss-of-function mutations in von Hippel Lindau (vHL) protein (which targets HIF-1a for degradation) [42], by exposure of healthy volunteers to acute hypoxia [43], or by pharmacologic or genetic manipulation of HIF-1a in zebrafish [44]. Similarly, intermittent hypoxia delayed apoptosis of TNF-a-treated human neutrophils [45], and neutrophils isolated from patients with obstructive sleep apnoea, which is characterised by intermittent hypoxia/reoxygenation, exhibited delayed apoptosis and increased expression of the adhesion molecule CD15 [46]. Hypoxia increases b 2 integrin protein expression, which is again mediated by HIF-1 [47], and may contribute to the hypoxic survival effect; b 2 integrin clustering or activation with endothelial ligands, such as ICAM-1, delays apoptosis through AKT and MAPK-ERK signalling, although b 2 integrin activation in the presence of death-inducing agonists, such as TNF-a, can also accelerate apoptosis.…”
Section: Apoptosismentioning
confidence: 99%
“…Decreased apoptosis and increased expression of adhesion molecules were observed. Although adhesion molecules may facilitate increased polymorphonuclear-endothelium interactions, decreased apoptosis may further augment these interactions and facilitate free radical and proteolytic enzymes (Dyugovskaya et al, 2008).…”
Section: Oxidative Stressmentioning
confidence: 99%